Eficácia horizontal dos direitos fundamentais - Nakahira, Ricardo (2007)
The purpose of this study is to systematize the concept, national an foreign, of the horizontal efficacy of fundamental rights. The issue is relevant considering that fundamental rights have been violated since the beginning of civilization. In the current days their protection and observance are still necessary. These violations can be derived from sovereign States and from private agents big companies, banks, unions, associations making therefore the awareness of these rights by those agents ultimately necessary. The fashion, the scope and the range of this efficacy are the subject of this paper. As it can be verified throughout the text, the direct application of fundamental rights in private relations was admitted. Lastly it was put forward considerations about the problem of recognizing the horizontal efficacy of fundamental rights